Current Status of Rattans of Andaman and Nicobar Islands - Naithani, H. B.; Garbyal, S. S.; Alappatt, Joju P. (Indian Forester, 2019)
Total 18 species of rattans were recorded from Andaman and Nicobar Islands. Authors have made survey of rattan species and recorded 17 species from the Islands, along with their vernacular names, phenology and uses. Out of 18 species, 3 species have been reduced recently and now total 15 species occur in Islands. Over exploitation is one of the major threats of their survival.